Study of direct current motor power requirement for manikin smart irrigation systems - Folkes E. Laumal; Darmawan Napitupulu; Oktaf B. Kharisma; Kusa B. N. Nope; Robinson A. Wadu (Universitas Ahmad Dahlan, 2019)
Manikin Irrigation Area (I.A) has ± 3000 ha of the area, utilizes the water source from the Tefmo Dam and distributes to the Primary-Secondary-Tertiary channels with controlled by watergates that operated by lift. This mechanism has resulted in jealousy and squabbles in farmer groups because of the inequality distribution that ultimately decreases crop production. The development of Microcontroller Technology has changed the Watergate model into an automated system based on certain parameters and algorithms. One of that being developed is the smart irrigation system based on Arduino at Manikin I.A that regulates the water to land based on the time from the Real-Time Clock sensor and uses Direct Current (DC) motor as a driver to watergate. While it may work, but the system has not considered the power requirement of DC motor when the water flows in the maximum discharge and pressure affecting the motor. This study examines the power requirement of an ideal DC motor for smart watergate in 5 open channels in Manikin I.A. Based on the open channel standard parameters, a total load measurement is performed when the water given speed (V) and pressure (p) then converted to energy. The study results that on 5 different open channels in Manikin I.A, with 0.30 m3/s maximum water discharge and 7.56 m/s2 flow rate, a watergate control requires DC motor that has 35 to 43 Watt power (39,4 Watt average power) or 3 to 3.5 Ampere current (3,26 Ampere average Current) in order to 24-hours work.